Impaired suppressor activity in children affected by coeliac disease. Issue 3 (March 1985) - Pignata, C; Troncone, R; Monaco, G; Ciriaco, M; Farris, E; Carminati, G; Auricchio, S
Abstract : Immunoregulatory cells were enumerated in 19 coeliac disease children on a gluten free diet by means of monoclonal antibodies that define total T lymphocytes (T3), helper/inducer T cells (T4), suppressor/cytotoxic T cells (T8) and monocytes (M1), as well as by means of surface receptors for Fc fragments of IgM and IgG (T mu and T gamma, respectively). In addition, suppressor cell function was assessed in 17 coeliac disease patients by examining the ability of concanavalin-A (Con-A)-activated suppressor cells to inhibit autologous cell response to mitogenic stimulus as compared with age-matched controls. No statistically significant differences were found in the percentages of subsets defined by monoclonal antibodies between coeliac disease patients and age-matched controls, whereas coeliac disease patients had a significant decrease of the subpopulation bearing membrane receptor for Fc fragment of IgG. Mean value was 8.5% in coeliac patients versus 13.4% in age-matched controls. In the functional assay, mononuclear cells from 10 out of 17 coeliac disease patients either totally or partially failed to suppress responder cells after Con-A-activation. This defect is not related to HLA-DR status, because no difference was found between patients-HLA-matched and unmatched normal individuals. In this assay, mononuclear cells of three coeliac disease patients with low suppressor activity were able to inhibit responder cells to the same extent as controls, when indomethacin was used to block prostaglandin production in the induction phase of Con-A-activated suppressor cells. Our results suggest that an abnormality in immunoregulation may play a role in the pathogenesis of coeliac disease.